STRATEGI PENGELOLAAN LIMBAH CAIR BERDASARKAN KONDISI SARANA DAN PRASARANA DI LABORATORIUM KESEHATAN MASYARAKAT PROVINSI RIAU MENGGUNAKAN METODE SWOT DAN MATRIKS IFAS–EFAS - Sri Hayati; Herniwanti (Journal of Hospital Administration and Management (JHAM), 2026)
Laboratory wastewater management is essential for environmental protection and public health due to the presence of hazardous chemical and microbiological contaminants. This study aimed to analyze wastewater management conditions based on facilities and infrastructure at the Public Health Laboratory of Riau Province and to formulate appropriate management strategies. A descriptive-analytical approach was applied using SWOT analysis followed by Internal and External Factor Analysis Summary (IFAS–EFAS). Data were collected through observation, interviews, and document review. The analysis showed an internal factor score of -0.35 and an external factor score of 0.05, placing the laboratory wastewater management system in Quadrant III (Weakness–Opportunities). This indicates significant internal weaknesses, particularly in wastewater treatment plant (WWTP) performance, limited technical facilities, and inadequate human resource capacity. However, substantial external opportunities exist, including regulatory support, technological advancements, funding opportunities, and institutional guidance. The recommended strategy emphasizes utilizing external opportunities to address internal weaknesses through WWTP upgrading, SOP standardization, strengthened effluent monitoring, digital documentation, and continuous capacity building.